Wuluh Star Fruit (Averrhoa bilimbi Linn) and Pineapple (Ananas comosus L.) Formulations on the Quality of Fruit Syrup - Eva Mayasari; Agustia Agustia; Tri Rahayuni (International Journal of Advance Tropical Food, 2020)
Syrup is an alternative processed food derived from fruits. Fruit syrup is produced from starfruit and pineapple juice formulations. This study aims to get the best quality of fruit syrup from starfruit juice extracts and pineapple. The study design used a Randomized Block Design with one treatment factor consisting of the ratio of starfruit and pineapple juice that is 3: 1; 2: 1; 1: 1; 1: 2; 1: 3 of a total of 300 mL of juice. The results showed that the more pineapple ratio added to the manufacture of fruit syrup, it can increase the pH value, vitamin C, total dissolved solids, viscosity, total sugar and sensory appearance